Propaganda covid-19 terhadap awareness masyarakat surabaya untuk mengikuti program kerja pemerintah - Alvian, Yusak; Laudry, Steven (Jurnal Komunikasi Profesional, 2020)
This study aims to analyze the influence of Covid-19 propaganda on the awareness of the people of Surabaya to participate in government work programs. The approach used in this study is a quantitative method. The population in this study were people of the City of Surabaya, East Java, totaling 3,095,026 people, while the samples taken were 100 Surabaya people. The data source in this study is primary data where data collection is done by distributing questionnaires. Data that has been collected will be tested for validity and reliability first. The data analysis technique used is simple linear regression analysis. Based on the results of the analysis in this study shows that there is a significant influence between Coagraphic Propaganda 19 to Awareness.